PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR ROLL DEPAN KELAS V DI SDN 192 PEKANBARU - Azwiranto Azwiranto; Ardiah Juita; Andrew Rinaldi Sinulingga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is that in the implementation of Physical Education learning, especially the Floor Gymnastic subject, teachers tend to give value to students who can carry out perfect movements in Floor Exercise learning. This makes the learning outcomes that occur at SDN 192 Kota Pekanbaru not so good. This happened due to the low interest in student learning, a boring learning model which resulted in the minimum completeness criteria (KKM) of subject teachers being taught unevenly. The purpose of this study was to find out whether through the discovery learning model applied by PJOK teachers can provide good roll forward learning outcomes. This type of research is classroom action assessment (PTK) which is a form of research that is reflective by taking certain actions in order to improve or improve classroom learning practices in a professional manner (Kanca, 2010: 108). The location of this research was carried out at SDN 192 Pekanbaru City, the reason for choosing this location was because SDN 192 Pekanbaru City. From the results of this study it can be concluded that there is an increase in forward roll through the discovery learning model on the learning outcomes of class V floor gymnastics at SDN 192 Pekanbaru city with an average score of 83 students' skills in the competent category with a classical completeness percentage of 83%.Key Words: Discovery Learning , Forward Roll.